Comparative Analysis of Arctic-Related Strategies at the National Level: Competition and Collaboration - Xiaoxue Ma; Liguang Chen; Weijie Wu; Yang Liu; Weiliang Qiao; Laihao Ma (Systems, 2023)
The melting of ice creates favorable conditions for the development of the Arctic by elevating the Arctic’s geostrategic value and stoking national competition. As a result, many states, both within and beyond the Arctic region, have recently released Arctic strategies or updated existing ones, clarifying their roles, interests, priorities, and policies for Arctic international cooperation. In this study, a database is generated with a collection of Arctic strategies from 16 states, and then grounded theory is applied to code the texts in these strategy documents. Using this code, word-frequency analysis, cross-tabulation, correlation analysis, and cooperative-network analysis are implemented to explore competition and collaboration in the Arctic among these 16 states. The results indicate that Arctic states are significantly concerned with governance, economic and social development, and security and stability, while environmental protection and scientific research are given more attention by non-Arctic states. In addition, the highest value of the Pearson correlation coefficient is identified as 0.85 for collaboration and Arctic public security affairs, which indicates that collaboration on Arctic security will dominate the development of Arctic affairs in the near future.